Prevalence of suicidal behavior in a northeastern Mexican border population during the COVID-19 pandemic - Villarreal Sotelo, Karla; Peña Cárdenas, Fabiola; Zamorano González, Benito; Vargas Orozco, Cynthia Marisol; Hernández Rodríguez, Ignacio; Landero Pérez, Carolina (Frontiers in Psychology, 2023)
Introduction Before the pandemic, suicide was already considered a global public health problem. The outbreak of COVID-19, a coronavirus-related infectious disease, began to impact people's physical and mental health. The factors that either contribute to or mitigate this risk need to be better understood, and this can only be accomplished through research. Therefore, this study aimed to study the prevalence of suicidal ideation and behavior in Tamaulipas, Mexico, during the COVID-19 pandemic. Methods A quantitative, descriptive, and cross-sectional study was conducted. The sample consisted of 659 participants, of whom 194 (29.5%) were men and 465 (70.5%) participants were oldwomen, ranging in age between 16 and 68 years (M = 22.56, SD = 7.26). An adapted version of the Spanish version of the Columbia Suicidal Severity Rating Scale was used to assess the seriousness of suicidal ideation and behavior. Results The higher rates of suicidal indicators were suicidal ideation with “wish to dead” (39.9%), while the lower was suicidal ideation with a specific plan (8.2%). A total of 18.2% of participants reported “suicidal attempts before COVID-19,” of whom 40% reported “suicidal attempts in the last 3 months.” Suicidal behavior rates were lower: 13.7% of participants reported “non-specific preparatory behavior” and 13.3% reported “actual suicide attempts.” Women were more likely than men to exhibit almost all indicators of suicidal ideation and behavior (OR = 1.63–2.54; 95% CI = 1.11–2.41, 1.76–3.68), as well as confinement (OR = 2.60; 95% CI = 1.73–3.91). Confinement for more than 40 days (OR = 0.55–0.66; 95% CI = 0.40–0.75, 0.47–0.93) and knowing a person infected with COVID-19 (OR = 1.57–2.01; 95% CI = 1.02–2.42, 1.20–3.34) were associated with a higher risk of exhibiting several suicidal indicators and having previously attempted suicide. Conclusion Being a woman, knowing a person infected with COVID-19, and being confined, especially for longer than 40 days, are all risk factors for suicidal ideation. Therefore, intervention programs are needed to reduce the suicide risk prevalence, especially these days because of the influence of the pandemic, and should be primarily focused on those who present the risk factors associated with suicidal behavior identified in this study.